Business Management Training In Bank Bakti Haji Malang - Tri Cicik Wijayanti (Kontribusia : Research Dissemination for Community Development, 2020)
Negotiations and teamwork are needed by anyone. A manager is expected to be able to suggest himself as an entrepreneur, the role of the problem solver, the role as the allocation of resources and the role of the final decision is the role of the negotiator. The role of the negotiator is necessary when dealing with outsiders in terms of determining cooperation or when the organization is confronted with conflicts of interest internally or otherwise. Negotiators must know examples, for example, when we are going to market the product. Follow-up from community service on extracting the potential of human resources to process the potential of human resources in terms of negotiating and team building can increase the added value of these human resources, which in turn can increase the income of employees, enthusiasm for work.